Meso-piperidine linked bodipys: Synthesis, fluorescent properties and biological evaluation - Ecik, Esra Tanriverdi; Kazan, Hasan Huseyin; Sengul, Ibrahim F.; Kandemir, Hakan; Cosut, Bunyemin (Elsevier Science Bv, 2019)
The synthesis and characterization of meso-piperidine linked Bodipy starting from 4-(2-(piperidine-1-yl)ethoxy) benzaldehyde was described. Meso-piperidine linked Bodipy was subsequently used for the construction of distyryl-piperidine-Bodipy and distyryl-morpholine-Bodipy via Knoevenagel type reaction. The photophysical properties including molar extinction coefficient, fluorescence lifetime and fluorescence quantum yield of Bodipys were investigated in ethanol solution. The targeted compounds were also assessed in live cell imaging and cytotoxicity studies by using breast cancer cell line, MCF-7 in vitro.
Keywords: Bodipy; Piperidine; Fluorescence; Live cell imaging